Evaluation of the effectiveness of computer-assisted instruction and conventional teaching method in enhancing mathematics achievement among senior Secondary school students in Ibadanland. (2018)
This study investigated the effects of a computer-assisted instructional technology application to teach statistics on a sample of senior secondary school students. A total number of 40 subjects, 25 in an experimental group and 15 in a control group were used and the pre and post-test experimental research design was adopted. Achievement test on statistics was applied on both groups. The experimental group was taught with the aid of computer-assisted instruction on electronic instructional slides using Microsoft PowerPoint. During the training session teaching-learning process were done using computer-assisted instructional technology and vivid explanation were given to the experimental group and the control group was subjected to conventional teaching method. After eight weeks, both groups were given the Statistics achievement test again. Using Analysis of Covariance (ANCOVA) at α = 0.05, F = 12.562, df = 2/38, p < 0.05 and Eta Square = 0.398. The findings revealed significant difference between the two groups and it’s favoured the experimental group over the control group in the Statistics achievement test scores. Therefore, researcher concludes that computer-assisted instructional technique can enhance the academic performance of the students, and recommended that the expansion of computer-assisted instructional aide/applications to other subjects will promote teaching-learning process and will enhance academic performance of the learners generally